Spore-forming bacteria in the gut: an interview with Hilary Browne. (August 2018) - Greenway, Alice
Hilary Browne speaks to Alice Greenway, Commissioning Editor of Future Microbiology, at the Microbiology Society Annual Conference 2018. Hilary Browne is a Staff Scientist at the Wellcome Sanger Institute in Cambridge (UK). His research focuses on culturing, curating and whole genome sequencing of the human gut microbiota and using these resources to study the human intestinal microbiota. At the Microbiology Society Annual Conference 2018, we asked him a few questions regarding his past and current research focuses, including the offered paper he presented at the conference entitled: 'Host adaptation of commensal bacteria through loss of sporulation and genome reduction'.